2017
DOI: 10.1080/02640414.2017.1334954
|View full text |Cite
|
Sign up to set email alerts
|

The importance and development of ball control and (self-reported) self-regulatory skills in basketball players for different positions

Abstract: This study first investigated the importance of ball control and (self-reported) self-regulatory skills in achieving the elite level in basketball. The second aim was to gain insight into the development of, and association between ball control and (self-reported) self-regulatory skills that contribute to achieving the elite level, with taking into account positional differences. Talented male players (N = 73; age 16.56 ± 1.96) completed the STARtest to measure ball control and a questionnaire to measure (self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Ball control is an exceptionally essential skill for football/soccer players since able to deliberately performing successful dribbling significantly while changing direction is required to achieve successful performances [7], [8], [9]. However, the importance of these skills needed in soccer can vary between players and different field playing positions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ball control is an exceptionally essential skill for football/soccer players since able to deliberately performing successful dribbling significantly while changing direction is required to achieve successful performances [7], [8], [9]. However, the importance of these skills needed in soccer can vary between players and different field playing positions.…”
Section: Introductionmentioning
confidence: 99%
“…Soccer players can be roughly divided into three prominent positions based on players' skills (guard, forward, centre), which each has slightly different roles to execute. By it, some players often spend many hours in training just in the wake of improving those skills which are especially important in their chosen sport (e.g., ball control in soccer ball) [7], [10]. According to [11], at least 10000 hours or ten years of deliberate practise are needed to meet expertise level.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sekine et al [ 18 ], using a pre-post design to study muscle morphology, jump and sprint performance in 12-15-year-old basketballers, reported that after one year players advanced in maturation improved significantly more in jump and sprint performance when compared to average and late maturing players. A study of technical skill (ball control) relating to self-regulatory skills in adolescent basketball players aged 13–20 years [ 19 ] found that ball control improved with age, especially between 13 and 17 years. Ball control interacted with positional differences, with guards revealing the highest rate of ball control development over the same ages.…”
Section: Introductionmentioning
confidence: 99%